Future Pathways in Malay Philological Inquiry - Mardiah Mawar Kembaren; M. Husnan Lubis (JPI: Jurnal Pustaka Indonesia, 2025)
This article examines future directions for Malay philological inquiry by addressing the gap between manuscript digitisation and the production of linguistically meaningful knowledge. It aims to propose a critical digital Malay philology model that moves beyond preservation toward corpus-based, Jawi-sensitive, and ethically grounded interpretation. Using a multilayered mixed-method design, the study synthesises philological interpretation, quantitative corpus mapping, and triangulation of recent manuscript digitisation data, Jawi literacy research, and Malay linguistic scholarship. The findings show that DREAMSEA’s 2024 documentation of more than 571,584 manuscript images from over 8,570 manuscripts across 168 owners and 57 regions provides a substantial empirical foundation for corpus-oriented philology. The 2025 inclusion of eighteen manuscripts, including eleven Malay manuscripts, in the Royal Asiatic Society Digital Library further confirms the transnational circulation of Malay textual heritage. However, digitised images generate philological knowledge only when transformed through transliteration, orthographic annotation, genre classification, semantic tagging, and discourse interpretation. The study also finds that Jawi spelling variation affects readability, searchability, and historical interpretation. The proposed model contributes by integrating classical philology, corpus linguistics, historical semantics, sociolinguistics, digital humanities, and community collaboration to reframe Malay manuscripts as living archives of language, law, religion, diplomacy, and civilisation.